EFFECTIVENESS OF THE COUNTENANCE STAKE MODEL IN EVALUATING THE AIHES CURRICULUM - Rofia Masrifah; Sitti Mania; Muljono Damopolii; St Syamsudduha (Academic Bright Collaboration, 2026)
This study evaluates the implementation of the Athirah Integrated Holistic Education System (AIHES) curriculum by using the Countenance n model. As a holistic curriculum, AIHES is designed to integrate academic excellence with Islamic values and character. This study aims to examine the congruence between intended curriculum design and actual implementation. A qualitative approach was employed, with data collected through classroom observations, semi-structured interviews with teachers and school leaders, and analysis of curriculum documents. The analysis applied the Countenance framework by comparing intended conditions, observed practices, and established standards to assess the level of alignment. The findings indicate that the AIHES curriculum effectively strengthens the school’s religious culture and supports character. development, reflecting the institutional identity of holistic Islamic education. Variations remain the integration of Islamic values within general subjects and teachers’ pedagogical practices. These findings highlight need for stronger evaluative supervision and continuous professional development to ensure a more consistent realisation of the curriculum’s holistic and value-based educational goals. This study highlights the importance of evaluation curriculum implementation, particularly in translating holistic and value-based principles into teaching practices. It also suggests that future research should explore the integration of formal and hidden curricula. This study contributes by applying Countenance model to evaluate a holistic Islamic curriculum, with a focus on classroom implementation. It provides empirical evidence of the gap between curriculum design and teaching practice, and offers a practical framework for evaluating value-based and integrative learning.